The spontaneous magnetic field direction in an anisotropic MHD dynamo - Shakhov, B.A.; Jurcisin, M.; Jurcisinova, E.; Stehlik, M. (Кинематика и физика небесных тел, 2012)
The phenomenon of magnetic field generation in an astrophysical plasma in the frame of developed magnetohydrodynamic (MHD) turbulence is considered. The functional quantum field renormalization group approach is applied to helical anisotropic MHD developed turbulence which is stabilized by the self-generated homogeneous magnetic field. The purpose of the study is to calculate the value as well as direction of the magnetic field in the stochastic dynamo model. The generated magnetic field is determined by ignoring divergent rotor part of Green function of the magnetic field. It is shown that the magnetic field direction is connected with unique existing vector n describing the anisotropic turbulence forcing. Розглядається явище генерації магнітних полів в астрофiзичнiй плазмi у межах моделi розвиненої МГД-турбулентностi. Застосовується квантовопольовий пiдхiд ренормалiзацiйної групи до розвиненої гiротропно-анiзотропної турбулентностi, яка стабiлiзуєть ся самогенерованим магнiтним полем. Метою цього дослiдження є обчислення як значення, так i напрямку магнiтного поля у стохастичнiй моделі динамо. Генероване магнiтне поле визначається при знехтуваннi дивергентної роторної частини функцiї Грiна магнiтного поля. Показано, що напрямок магнiтного поля пов'язаний з наявністю вектора n, який описує анiзотропне накачування енергiї у турбулентнiсть. Рассматривается явление генерации магнитных полей в астрофизической плазме в рамках модели развитой МГД-турбулентности. Применяется квантовополевой подход ренормализационной группы к развитой гиротропно-анизотропной турбулентности, которая стабилизируется самогенерируемым однородным магнитным полем. Целью этого исследования является вычисление как значения, так и направления этого магнитного поля в стохастической модели динамо. Генерируемое магнитное поле определяется при пренебрежении дивергентной роторной частью функции Грина магнитного поля. Показано, что направление магнитного поля связано с наличием вектора n, описывающего анизотропное накачивание энергии в турбулентность.